Interaksi tropik antara hama dan parasitoid pada pertanaman sayuran: faktor pembentuk dan implikasinya terhadap keefektifan parasitoid - Nugraha, Muhamad Nurhuda; Buchori, Damayanti; Nurmansyah, Ali; Rizali, Akhmad (Perhimpunan Entomologi Indonesia, 2014)
The condition of agroecosystem may affect the diversity and effectiveness of parasitoid communities as natural enemies of insect pests. Agricultural intensification such as monoculture cultivation as well as application of insecticide could also cause declining to parasitoid diversity and ineffective performance of parasitoids in agricultural field. The objective of this research was to study trophic interaction between pests and parasitoids in different field of vegetable crops and to investigate the factors that determining those interactions as well as its implication on parasitoid effectiveness. Vegetable crop fields were grouped into three different categories i.e. based on the pattern of cultivation, diversity of vegetable crops around the field and age of plant. On each crop field, insects were sampled using 50 m of transect by collecting eggs, larvae and pupae of pests. In total, 15 species of pests and 15 species of parasitoids were recorded from eight species of vegetable crops. Based on the analysis, trophic interaction between pests and parasitoids were affected by cultivation system, condition of crop field (species diversity of crops in its surrounding) and age of vegetable plants. Although it was not significance, the effectiveness of parasitoids according to their parasitism level, tend to higher in trophic interaction that determined from crop field with organic systems and with diverse of crop plants.